A case of vaping-induced acute respiratory distress syndrome requiring extracorporeal life support. (April 2021) - Krishnan, Sudhir; Thind, Guramrinder Singh; Soliman, Mona; Tolle, Leslie; Mireles-Cabodevila, Eduardo; Adi, Ahmad; Anandamurthy, Balaram; Bribriesco, Alejandro; Yun, James
Introduction: An upsurge of e-cigarette, or vaping, product use–associated lung injury has been reported in the United States. The potential role of extracorporeal life support in e-cigarette, or vaping, product use–associated lung injury merits consideration. Case report: We present a case of vaping-induced severe acute respiratory distress syndrome that was salvaged with extracorporeal life support and had excellent recovery. Discussion: The mechanistic reasons for the sudden outbreak of e-cigarette, or vaping, product use–associated lung injury are under active investigation. A predominantly diffuse, bilateral pattern of lung injury has been reported, with some cases meeting the criteria for severe acute respiratory distress syndrome. To date, 68 deaths from e-cigarette, or vaping, product use–associated lung injury have been confirmed by the centers of disease control. However, resolution of lung injury has been reported in most cases, thereby justifying candidacy for extracorporeal life support, if required. Conclusion: Extracorporeal life support can be successfully utilized as a bridge to recovery in vaping-induced severe acute respiratory distress syndrome.